Interpretation of aquifer layers in peatland areas using the Wenner configuration geoelectric method in Rimba Panjang Village, Tambang District, Kampar Regency - Firmansyah, Restu; Muhammad, Juandi (Indonesian Physics Communication, 2024)
Geoelectric is a geophysical method used to determine the geological conditions of the earth's subsurface based on the variations of rock resistivity value. Interpretation of the aquifer layer is carried out on 2 paths with a length of 300 meters each. The lithology of the study area consists of layers of clay, peat, clay, sand, coarse sandstone, dry gravel, mudstone, limestone, tufan sand to siltstone. According to the data processing results, it shows that the aquifer in Rimba Panjang Village is at a depth ranging from (12.8 – 24.9) meters below ground level with medium groundwater potential. Interpretation using Res2Dinv Software as well as geological maps of the surrounding area informed the subsurface conditions and the presence of groundwater aquifers of the study area. It was found that the resistivity interval of trajectory 1 are (164.341) Ωm, (709 – 1477) Ωm, to (1477 – 3075) Ωm while of trajectory 2 are (864 – 1642) Ωm, (1642 – 3118) Ωm, to (3118 – 5921) Ωm. It can be concluded that the deeper the soil layer, the higher the moisture content. Because the deeper the soil layer, the lower the maturity of the peat, so that the soil is able to hold more water.